Mystical Experience from Religious Community of Qadiriyah wa Naqsyabandiyah Dawe Kudus - Atika Ulfia Adlina (Balai Penelitian dan Pengembangan Agama Semarang, 2012)
The research aimed to know: 1. Ahwal (mystical experience) experienced by followers of Tarekat Qadiriyah wa Naqsyabandiyah in Piji, Dawe, Kudus; 2. The correlation between suluk and their kinds of ahwal; and 3. The different intensity of ahwal for the followers in each stage of the tarekat. This was a field reserch which used purpo- sive sampling tehnique. The data were then analysed qualitatively and phenomeno- logically. The findings of the research showed that there were some factors motivated people to join the Tarekat: the intention to be close to God, preparing themselves for death, charismatic figure, etc. Secondly, the classification of the mystical experi- ences was adjusted with the lataif dzikir stages, they were laţîfah al-qalb, laţîfah ar- rûh, laţîfah as-sirr, laţîfah khafiy, laţîfah akhfa, laţîfah an-nafsi dan laţîfah al-qâlib. There were same ahwal experienced by the followers in some stages. Therefore, it was concluded that there was a relationship between suluk and ahwal experienced by the followers of the tarekat in Piji Dawe Kudus.